Defective induction of the proteasome associated with T‐cell receptor signaling underlies T‐cell senescence. (6th November 2019) - Arata, Yoshiyuki; Watanabe, Ayaka; Motosugi, Ryo; Murakami, Ryuichi; Goto, Tsuyoshi; Hori, Shohei; Hirayama, Shoshiro; Hamazaki, Jun; Murata, Shigeo
Abstract: The proteasome degradation machinery is essential for a variety of cellular processes including senescence and T‐cell immunity. Decreased proteasome activity is associated with the aging process; however, the regulation of the proteasome in CD4 + T cells in relation to aging is unclear. Here, we show that defects in the induction of the proteasome in CD4 + T cells upon T‐cell receptor (TCR) stimulation underlie T‐cell senescence. Proteasome dysfunction promotes senescence‐associated phenotypes, including defective proliferation, cytokine production and increased levels of PD‐1 + CD44 High CD4 + T cells. Proteasome induction by TCR signaling via MEK‐, IKK‐ and calcineurin‐dependent pathways is attenuated with age and decreased in PD‐1 + CD44 High CD4 + T cells, the proportion of which increases with age. Our results indicate that defective induction of the proteasome is a hallmark of CD4 + T‐cell senescence. Abstract : Proteasome dysfunction promotes senescence‐associated phenotypes in CD4 + T cells. The proteasome is induced via T‐cell receptor signaling, and the induction is attenuated with age. Our results indicate that defective induction of the proteasome is a hallmark of CD4 + T‐cell senescence.